Enhanced Perspective Generation by Consensus of NeX neural models - Pacheco dos Santos Lima Junior, Marcos Sergio; Fernández-Rodríguez, Jose David; Ortiz-de-Lazcano-Lobato, Juan Miguel; López-Rubio, Ezequiel; Domínguez-Merino, Enrique (My University, 2022)
Neural rendering is a relatively new field of research that aims to produce high quality perspectives of a 3D scene from a reduced set of sample images. This is done with the help of deep artificial neural networks that model the geometry and color characteristics of the scene. The NeX model relies on neural basis expansion to yield accurate results with a lower computational load than the previous NeRF model. In this work, a procedure is proposed to further enhance the quality of the perspectives generated by NeX. Our proposal is based on the combination of the outputs of several NeX models by a consensus mechanism. The approach is compared to the original NeX for a wide range of scenes. It is found that our method significantly outperforms the original procedure, both in quantitative and qualitative terms.
Keywords: Redes neuronales (Informática) - Congresos; Aprendizaje automático (Inteligencia artificial) - Congresos; Sistemas autoorganizativos - Congresos; Deep learning; Convolutional neural networks; Neural rendering; Consensus model